Performance analysis of the female Yurchenko layout on the table vault - Penitente, G. (International Journal of Performance Analysis in Sport, 2014)
This study proposed a performance analysis method of the gymnastics vault that accounts for the open-score judging system. The model aims to identify the mechanical faults that explain the deductions assigned by judges relative to the on-board and pre-flight phases of the Yurchenko-style vault. In the attempt to identify the weakness of technique and to diagnose the likely causes of poor performance, an extensive analysis was undertaken using a deterministic model. Twelve Yurchenko layout vaults with and without full twist in the post-flight performed by female gymnasts during the team competition of the 2006 Italian Championship were filmed with three cameras operating at 100 Hz. Spearman's correlation coefficient was used to measure the strength of the relationship between the mechanical variables of the model and the judges' point deductions. Significant correlations indicated that the loss of points depended mostly on the range of flexion of the shoulders at the impact with board, a disproportionate flexion of the knees during the on-board phase and the inaccuracy of the pre-flight. Comparing results with existing literature large differences were noticed, this underlines the need for up to date information on the modern vaulting techniques.